Seroprevalence of IgG and IgM anti-Toxoplasma gondii antibodies and associated risks factors in pregnant women of northern Durango, Mexico - Rolando Adair Facio-Campos; Cosme Alvarado-Esquivel; Edgar Olivas-Calderon (Instituto Nacional de Salud Pública, 2020)
Toxoplasmosis is caused by intracellular parasite Toxoplasma gondii (T. gondii). T. gondii infection in pregnancy can result in serious consequences for the developing fetus or newborn, including spontaneous abortion, hydrocephalus, and even death (1). The infection could be acquired by ingestion of food (raw or uncooked meat from infected animals), direct contact with cat feces or soil contaminated with oocysts. In 2012 Caballero-Ortega et al., (2) found an increase in the toxoplasmosis distribution in the north region (35%) finding the highest prevalence in coastal regions (67.5%) of México. There is no data historic available about this seroprevalence, specifically of the "Comarca Lagunera" of Durango State. Moreover, previous study of T. gondii seroprevalence in Durango City showed that 6.1% of pregnant woman of urban areas and 8.2% of rural areas were found positives (3). In 2018, 434 pregnant women who used the Health Services of Durango State in the "Comarca Lagunera Region" were studied with an average age of 22.2 years (± 5.95); we found four (0.92%) IgG and none (0.0%) IgM antibodies anti-T. gondii (Table I). Consumption of dried meat (OR = 16.5; 95% CI 1.7 - 161.48; p= 0.01) and sheep and goat meat (OR = 15.61; 95% CI 1.1 - 224.05; p= 0.043) were associated factors to the infection. Number and different types of pets and cats was not associated with anti-T. gondii antibodies. The "Comarca Lagunera" of Durango being a cattle zone, frequently local meat is consumed in general, representing a possible risk factor. It is particularly interesting since this study's seroprevalence was 0.91% in a small area of Durango State, differing from the global prevalence in the State. Probably, this results could be due to Durango State having a geographical diversity, Durango capital is located in a valley, unlike the "Comarca Lagunera" region, which is a semi-desert zone with high environmental temperature (Up to 45°C), that could explain the reduced survival of oocysts which implies a subsequent investigation to this work.